What is gluten and how it is harmful - Mukoid, Roman (My University, 2015)
The article is devoted to the study of genetic disease control – particularly celiac disease. The disease is characterized by protein intolerance of cereals - gluten. For preventive and therapeutic nutrition the use of food products made with gluten-free germinated cereals is proposed.
Keywords: protein; gluten; celiac disease; disease; food products; gluten-free; germination; grain; білок; глютен; целіакія; захворювання; безглютенові продукти; пророщування; зерно; кафедра біотехнології продуктів бродіння і виноробства